2022
DOI: 10.3390/nu14163254
|View full text |Cite
|
Sign up to set email alerts
|

Association of Eating Behavior, Nutritional Risk, and Frailty with Sarcopenia in Taiwanese Rural Community-Dwelling Elders: A Cross-Sectional Study

Abstract: This cross-sectional study assessed the association of eating behavior, nutritional risk, and frailty with sarcopenia in 208 community-dwelling individuals aged ≥65 years who were recruited from random rural community care centers in Chiayi County, Taiwan. The participants’ eating behavior was categorized into six categories. The gait speed (GS), grip strength, and appendicular skeletal muscle mass (ASM) were assessed based on these three parameters, which revealed that 50.9% of the participants had sarcopenia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…This is in line with the previous studies stating that low educational attainment [ 41 ], neuroticism [ 42 ], low testosterone levels [ 43 ], short stature [ 44 ], high alcohol [ 45 ], processed meat [ 46 ] and salt [ 47 ] intake, sedentary behavior (such as watching television) [ 48 ], smoking and physical inactivity [ 49 ] are associated with an increased risk of sarcopenia or low muscle strength, whereas coffee, magnesium, potassium, protein, vitamin D, water, oil fish, fruits and vegetables intake [ 46 , 50 , 51 , 52 , 53 , 54 ] have protective effects against sarcopenia.…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with the previous studies stating that low educational attainment [ 41 ], neuroticism [ 42 ], low testosterone levels [ 43 ], short stature [ 44 ], high alcohol [ 45 ], processed meat [ 46 ] and salt [ 47 ] intake, sedentary behavior (such as watching television) [ 48 ], smoking and physical inactivity [ 49 ] are associated with an increased risk of sarcopenia or low muscle strength, whereas coffee, magnesium, potassium, protein, vitamin D, water, oil fish, fruits and vegetables intake [ 46 , 50 , 51 , 52 , 53 , 54 ] have protective effects against sarcopenia.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the positive effects of certain dietary components, such as higher intake of fruits, vegetables, and whole grains, on frailty among older adults were substantiated and supported by various longitudinal studies [9,24,25]. Conversely, some other studies have identified the potential risk factors associated with frailty, including excessive consumption of processed food, and high-fat, high-sugar foods [26]. Unhealthy dietary habits characterized by a low intake of essential nutrients, such as protein and vitamins, may contribute to frailty development and exacerbate age-related declines in physical function and cognitive health [10].…”
Section: The Context Of China: Differences By Hukou Status and Gendermentioning
confidence: 96%